(untitled) (Revista Iberoamericana de Bioética, 2019)
Ethical dilemmas are not new in perinatology. Even with the new advances in the care of pregnant women, pediatricians find themselves facing extremely small babies at the limit of survival. With parents informed of the risks of sequelae in these babies and with their decision to assist them or not, ethical decisions are transferred to the delivery room. There, the pediatrician, along with the parents, must make decisions according to the best evidence available, and the ethical approach that is established regarding those relations, rather than stressing autonomy, to a large extent favors compassion with regard to the human beings in the center of the action.